The Importance of Creativity and Innovation in Education: How to Prepare Students for the 21st Century Workforce - Suyuti Suyuti (Penelitian dan Pengembangan Ilmu, 2024)
Creativity and innovation have been recognized as important elements in establishing a dynamic educational environment and in improving students' skills in critical thinking and problem solving. However, systematic research that combines various concepts and approaches related to creativity and innovation in educational contexts is still limited. The aim of this research is to conduct a systematic literature review to investigate the role of creativity and innovation in education, as well as to explore the implications of these findings for educational practice. This research method involves searching and analyzing relevant articles from leading international journals indexed in the Scopus database. The results of the discussion show that the integration of creativity and innovation in education has a significant impact in improving the quality of learning, student engagement, and student preparation to face future demands. The implication of these findings is the need for an innovative and creativity-oriented educational approach to prepare students to face future challenges in a dynamic and competitive global era.